Pertinencia de la practica pedagógica docente y su relación con el desempeño académico de los estudiantes de la institución educativa Fermin Tilano (2016)
This document outlines the findings regarding the relevance of teaching pedagogical Research Practice (PPD) and Your Relationship With Academic Performance (DA) students of School Fermín Tilano of Chorrera. From them overall objective relevance of PPD and its relationship with the DA Student Determined, which the identification of postulates Theoretical, epistemological that reveal the pedagogical practice teaching the investigated context requires, to characterize Such practical and identify elements underlying the Academic Performance and establish relations in a Coherence: relevance educational requirements. To develop the investigative process that meets the study categories are considered the appointment of theoretical framework guiding the study. Freire, Gimeno, Zuluaga and Zambrano: From the author postulates Pedagogical Practice As contemplated. Thus in the category itself Academic Performance Highlights Contributions of authors such as stories, Tellez Diaz Barriga and Gimeno. Meanwhile relevance category is approached from the position of UNESCO and author of As Tünnermann and Humberto Maturana, who see it as one of the attributes of Educational Quality. Qualitative Research court is conceived from UN paradigm critical partner under the Action Research Methodology, since the intention to address the educational reality for collective and comprehensive Problem Construction is based. Techniques and Instruments As a literature review, observations, surveys and interviews were used, one teacher APLICADAS management, Parents and Students in third, fifth, ninth and eleventh grade. Results show important disarticulation between theory and Exercise of praxis, few processes of planning, unmotivated teaching Actos, A Evaluative practice summative character, little accompaniment Parents, excessive freedom of the Common and inconsistencies between the teacher training purposes and actions the Theoretical Foundations epistemological indicated in Institutional Documents.